The effect of prosperity on international tourism expenditure - Sokhanvar, Amin; Aghaei, Iman; Aker, Sule (Emerald Group Publishing Ltd, 2018)
Purpose - This paper aims to investigate prosperity-international tourism expenditure nexus to discover the prosperity sub-indices which affect tourism expenditure. Design/methodology/approach - Using annual panel data for the sample period between 2009-2013 on 98 countries, this study implements a two-stage least squares estimation method with fixed effects specification in a panel regression analysis to find the relationships between international tourism expenditure and prosperity sub-indices. Findings - The estimation results reveal a statistically significant relationship between the tourism expenditures of the citizens and prosperity, when prosperity is measured using its sub-indices, including Entrepreneurship and Opportunities, Government Efficiency, Education, Health, Safety and Security, Personal Freedom, Social Capital and Economy of the country. Education, Safety and Security and Health are the most significant factors which affect tourism expenditures of the country of origin. Practical implications - To decrease the money outflow, policymakers may have plans to improve health infrastructure and, at the same time, increase quality of education and access to education in the country. Tourism policies which do not consider these prosperity sub-indices as explanatory variables maymakemistakes in controlling actual tourismexpenditures. Originality/value - The paper's originality lies in using new independent variables (prosperity subindices) in estimating tourism expenditure by using an appropriate panel data approach that deals with endogeneity problems.
Keywords: Prosperity; Safety; Education; Health; International tourism expenditures